Advancements in Detection and Mitigation: Fortifying Against APTs - A Comprehensive Review - Aashesh Kumar; Muhammad Fahad; Haroon Arif; Hafiz Khawar Hussain (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Organizations' cyber security posture is severely challenged by Advanced Persistent Threats (APTs), necessitating a multifaceted defense strategy. Traditional methods, machine learning, artificial intelligence (AI), behavioral analytics, real-time monitoring, incident response, collaborative defense mechanisms, endpoint security enhancements, network segmentation and access control, encryption, data protection, and user training and awareness are just a few of the strategies and advancements in APT detection and mitigation that are examined in this review article. Every tactic is thoroughly reviewed, emphasizing its value in thwarting APT attacks and offering best practices for execution. By utilizing these cutting-edge methods and encouraging cooperation amongst enterprises, it is feasible to improve defenses against APTs and lessen the likelihood that they will affect vital assets and data.